2004
DOI: 10.1038/sj.emboj.7600484
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of voltage sensor movements in a potassium channel

Abstract: Voltage-gated potassium channels are six-transmembrane (S1-S6) proteins that form a central pore domain (4 Â S5-S6) surrounded by four voltage sensor domains (S1-S4), which detect changes in membrane voltage and control pore opening. Upon depolarization, the S4 segments move outward carrying charged residues across the membrane field, thereby leading to the opening of the pore. The mechanism of S4 motion is controversial. We have investigated how S4 moves relative to the pore domain in the prototypical Shaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 49 publications
7
27
0
Order By: Relevance
“…Amino acid side chains are represented approximately in the ROSETTA membrane method, and hence the accuracy of the models is limited to 2-4 Å at best (45). Among the 10 largest clusters of models (see Methods), the third cluster agreed with experimental data demonstrating proximity of residues at the extracellular ends of S4 from one subunit and S5 from the adjacent subunit (32,(35)(36)(37) (Fig. 2 A and B).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Amino acid side chains are represented approximately in the ROSETTA membrane method, and hence the accuracy of the models is limited to 2-4 Å at best (45). Among the 10 largest clusters of models (see Methods), the third cluster agreed with experimental data demonstrating proximity of residues at the extracellular ends of S4 from one subunit and S5 from the adjacent subunit (32,(35)(36)(37) (Fig. 2 A and B).…”
Section: Resultssupporting
confidence: 72%
“…S4 in our closed-state model of K v 1.2 is in close proximity to S5 from the adjacent subunit (Fig. 3 A and B), in agreement with results suggesting this topological arrangement in the closed state (35)(36)(37)49). These segments packed significantly more tightly in our closed-state model compared with the open-state structure, which is realistic because the hydrophobic face of the S4 helix rotated Ϸ180°from the lipid environment in the open state to the protein environment at the S4-S5 interface in the closed state (Fig.…”
Section: Model Of Kv12 In the Closedsupporting
confidence: 79%
See 1 more Smart Citation
“…Cross-bridge formation between cysteine residues on the voltage sensor paddle and the extracellular side of S5 do not depend highly on the precise location of the cysteines (19)(20)(21)(22), and a single cysteine residue near the extracellular ''tip'' of the voltage sensor paddle can result in the formation of covalent subunit dimers, presumably through linkage of voltage sensor paddles from adjacent subunits (20). The nonspecificity of cross-bridge formation and covalent subunit dimerization mediated by single cysteine residues on the voltage sensor paddle suggests that the paddle is a highly mobile unit (Fig.…”
Section: Defining the Position Of The Kvap Voltage Sensor By Analogy mentioning
confidence: 99%
“…In subsequent studies based on disulfide linkage between S4 and S5 the VSD of one subunit was shown to make close contact with the pore domain of a neighbouring subunit, not with its own subunit [60,[71][72][73][74]. This proposed interaction between two neighbouring subunits was later on supported by the X-ray structure of Kv1.2 [37].…”
Section: The Vsd Connects To the Upper End Of S5 In A Neighbouring Pomentioning
confidence: 62%